1995
DOI: 10.1128/jb.177.10.2942-2945.1995
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequences and expression of genes from Streptomyces purpurascens that cause the production of new anthracyclines in Streptomyces galilaeus

Abstract: Six open reading frames, rdmA to rdmF, in a 6,077-bp segment of Streptomyces purpurascens DNA which caused the production of hybrid anthracyclines were identified. The minimal fragment that produced anthracyclines modified at the 10th position contained rdmB to rdmD; rdmE is the gene for aklavinone-11-hydroxylase. RdmC is similar to a putative open reading frame in the daunorubicin biosynthetic cluster of Streptomyces peucetius and is likely to participate in the removal of the side chain at the 10th position.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 34 publications
0
59
0
2
Order By: Relevance
“…On the other hand, RdmB from the β-rhodomycin pathway in Streptomyces purpurascens is a very unusual enzyme that is evolutionarily closely related to DnrK with a sequence identity of 52% (24). Determination of the crystal structure of RdmB confirmed that the enzyme binds SAM (25) and that the ternary complex is indeed very similar to that of DnrK with a root-meansquare deviation of 1.14 Å for 335 equivalent Cα atoms (26).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, RdmB from the β-rhodomycin pathway in Streptomyces purpurascens is a very unusual enzyme that is evolutionarily closely related to DnrK with a sequence identity of 52% (24). Determination of the crystal structure of RdmB confirmed that the enzyme binds SAM (25) and that the ternary complex is indeed very similar to that of DnrK with a root-meansquare deviation of 1.14 Å for 335 equivalent Cα atoms (26).…”
mentioning
confidence: 75%
“…Determination of the crystal structure of RdmB confirmed that the enzyme binds SAM (25) and that the ternary complex is indeed very similar to that of DnrK with a root-meansquare deviation of 1.14 Å for 335 equivalent Cα atoms (26). Despite these features, RdmB completely lacks methyltransferase activity (24,27,28); it is an anthracycline 10-hydroxylase, which requires SAM, molecular oxygen, and a thiol reducing agent for activity (26). Contrary to DnrK, RdmB is able to use both monoglycosylated and triglycosylated anthracyclines as substrates.…”
mentioning
confidence: 87%
“…Enzymes encoded by this gene cluster include RdmA, an aklanonic acid methylester cyclase, and aklavinone-11-hydroxylase RdmE, which converts aklavinone to ⑀-rhodomycinone (11). Genetic evidence suggests that rdmB and rdmC code for two enzymes that catalyze the steps leading from ⑀-rhodomycinone glycoside to ␤-rhodomycinone glycoside (16). Both in vivo and in vitro experiments have shown that these two enzymes can also catalyze the conversion of aclacinomycin to 10-hydroxy-10-decarboxymethylaklavin (14).…”
mentioning
confidence: 99%
“…In Streptomyces purpurascens, the rdm operon contains several genes that code for tailoring enzymes of rhodomycin biosynthesis (5,16). Enzymes encoded by this gene cluster include RdmA, an aklanonic acid methylester cyclase, and aklavinone-11-hydroxylase RdmE, which converts aklavinone to ⑀-rhodomycinone (11).…”
mentioning
confidence: 99%
“…The deduced KasR protein (399 amino acids, M r of 42,562, pI of 6.06) showed significant similarity to hexose C-3 dehydrases which are involved in 3-deoxygenation of deoxysugar moieties of some secondary metabolites. Homology analysis for KasR revealed similarity with LanQ [21], an NDP-hexose 3,4-dehydratase involved in landomycin biosynthesis in Streptomyces cyanogenus (38% identity); RdmI [22], a hexose C-3 dehydratase involved in rhodomycin biosynthesis in Streptomyces purpurascens (37% identity); UrdQ [23], an NDP-hexose 3,4-dehydratase involved in the formation of the L-rhodinose moiety of urdamycin in Streptomyces fradiae (37% identity); AscC [24], and a CDP-4-keto-6-deoxy-D-glucose-3-dehydrase involved in ascarylose biosynthesis in Yersinia pseudotuberculosis (36% identity). These enzymes are dependent on pyridoxamine 5Ј-phosphate (PMP) and contain an ironsulfur cluster.…”
Section: Kasrmentioning
confidence: 99%